Investigating Financial Reporting Practices in Hybrid Financial Institusions in Indonesia - Fauzi, Nurul; Makmur, Andrew; Rosita, Irda; Handayani, Desi; Gustati, Gustati (Entrepreneurship and Small Business Research, 2022)
Hybrid financial institutions are sociopreneur organizations that carry out business activities with the aim of making profits and helping the community. Although these financial institutions make significant economic and social contributions to society, their financial reporting models still do not adequately present economic and non-economic information. This study aims to understand how financial reporting practices in financial institutions that have two functions or are often called hybrid financial institutions (profit motive and social motive) in Indonesia, especially in customary financial institutions Lumbung Pitih Nagari (LPN) in West Sumatra. The research design uses a case study at a hybrid financial institution of LPN. LPN is a customary financial institution whose main purpose of establishment is to help people who live in a village. In addition, this financial institution is also required to generate profit. The data collection technique is an in-depth interview with informants consisting of managers, communities, and other stakeholders. The results of this study show that LPN Limau Manis as a hybrid financial institution still uses financial reporting practices that are no different from conventional financial institutions in general. The types of financial statements produced following conventional financial institutions consist of income statements, statements of changes in equity, balance sheets, cash flow statements and notes to financial statements. While information about the social functions they perform is not reported in specific reports. It is only reported in a standard format in the form of social activity reports submitted at the General Meeting.